Precision medicine for multiple sclerosis: an update of the available biomarkers and their use in therapeutic decision making. Issue 6 (2nd November 2017) - Pulido-Valdeolivas, Irene; Zubizarreta, Irati; Martinez-Lapiscina, Elena H; Villoslada, Pablo
ABSTRACT: Introduction : Precision medicine is an approach to disease prevention and treatment that takes into account individual variability in terms of genetics, environment and lifestyle. This approach depends on clinical, imaging and biological markers to define the optimal therapeutic approach for a given patient. Areas covered : Although many biomarkers have been proposed for MS, at present only oligoclonal bands (OCBs), magnetic resonance imaging, optical coherent tomography measurements and the JCv antibody index have been implemented in clinical practice. Expert commentary : Validation of biomarkers in multicentric prospective studies is necessary to improve the application of precision medicine for MS patients. New tools will open new avenues to improve our ability to provide personalized therapy to individuals with MS, including those aimed at the extraction of medical information from electronic health records, or those involving the application of machine learning tools to combine different types of information and biomarkers.